Symptomatic treatment of neurologic symptoms in Wilson disease - Litwin, Tomasz; Dušek, Petr; Członkowska, Anna (Handbook of clinical neurology, 2017)
Wilson disease (WD) is a potentially treatable neurodegenerative disorder. In the majority of cases, treatment with drugs that induce a negative copper balance (usually chelators or zinc salts) leads to improvements in liver function and neurologic signs. However, some patients show severe neurologic symptoms at diagnosis, such as tremor, dystonia, parkinsonism, and chorea. In this patient group, some neurologic deficits may persist despite adequate treatment, and further neurologic deterioration may be observed after treatment initiation. Such patients may require additional treatment to alleviate neurologic symptoms. Apart from general recommendations for WD anticopper treatment, there are currently no guidelines for managing neurologic symptoms in WD. The aim of this chapter is to summarize possible treatments of neurologic symptoms in WD based on the presently available medical literature.
Keywords: dystonie; Tremor; Humans; Dystonia; Hepatolenticular Degeneration; Nervous System Diseases; Dystonic Disorders; lidé; dystonické poruchy; parkinsonism; dopamine; botulinum toxin; tremor; Wilson disease; nemoci nervového systému; dystonia; chelátory; deep-brain stimulation; Chelating Agents; hepatolentikulární degenerace